PENDIDIKAN NILAI-NILAI SOSIAL BAGI ANAK DALAM KELUARGA MUSLIM (Studi Kasus di RT 09 Dukuh Papringan Catur Tunggal Depok Sleman Yogyakarta) - Zakiyah Kholidah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2013)
This research is motivated by some fundamental issues related to education is not optimal social value of children in the family. It becomes a matter that needs to be addressed in the context of education, because it can have an impact on child development. With social values, social mental development of children in the family can be developed and improved surely. Related to the central issue, the author tries to identify the need for the implementation of the social values of education for children in Muslim families which then become the focus in this study. This study aimed to describe the social values of education for children in Muslim families on RT 09 Dukuh Papringan Catur Tunggal Depok Sleman Yogyakarta. The results of this research can be used as an evaluation of the education and development of students who are able to produce high quality and have the ability to face the future. This research is taking the field with the object of research is Social Values Education for Children in the Muslim Family. Data were collected by observation, interviews, and documentation.